IFITM3 functions as PIP3-scaffold to amplify PI3K signaling in B-cells - Lee, Jaewoong (Nature, 2020)
Ifitm3 was previously identified as an endosomal protein that blocks viral infection(1–3). Studying clinical cohorts of B-cell leukemia and lymphoma patients, we identified IFITM3 as a strong predictor of poor outcome. In normal resting B-cells, Ifitm3 was minimally expressed and mainly localized in endosomes. However, B-cell receptor (BCR) engagement induced expression of Ifitm3 and phosphorylation at Y20, resulting in accumulation at the cell surface. In B-cell leukemia, oncogenic kinases phosphorylate IFITM3-Y20, causing constitutive plasma membrane localization. Ifitm3ˉ(/)ˉ naïve B-cells developed at normal numbers; however, germinal center formation and production of antigen-specific antibodies were compromised. Oncogenes that induce development of leukemia and lymphoma failed to transform Ifitm3ˉ(/)ˉ B-cells. Conversely, the phospho-mimetic IFITM3-Y20E induced oncogenic PI3K-signaling and initiated transformation of pre-malignant B-cells. Mechanistic experiments revealed that Ifitm3 functions as PIP3-scaffold and central amplifier of PI3K signaling. PI3K signal-amplification depends on Ifitm3 scaffolding PIP3-accumulation via two lysine residues (K83 and K104) in its conserved intracellular loop. In Ifitm3ˉ(/)ˉ B-cells, lipid rafts were depleted of PIP3, resulting in defective expression of >60 lipid raft-associated surface receptors, impaired BCR-signaling and cellular adhesion. We conclude that phosphorylation of IFITM3 upon B-cell antigen-encounter induces a dynamic switch from antiviral effector functions in endosomes to a PI3K-amplification loop at the cell surface. IFITM3-dependent amplification of PI3K-signaling in part downstream of the BCR is critical to enable rapid expansion of B-cells with high affinity to antigen. In addition, multiple oncogenes depend on IFITM3 to assemble PIP3-dependent signaling complexes and amplify PI3K-signaling for malignant transformation.